Phosphomolybdic acid boosts polyunsaturated fatty acid and neutral lipid production in Phaeodactylum tricornutum - Kun-Tao Peng; Bing-Hong Xiong; Gao Cheng; Gao Cheng; Yuan-Hong Zhong; Yuan-Hong Zhong; Lin Yu; Lin Yu (Frontiers in Marine Science)
Phaeodactylum tricornutum is considered a potential lipid production platform due to its high growth rates and elevated natural neutral lipid and polyunsaturated fatty acid (PUFA) contents. Furthermore, microalgae are emerging as promising sources of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). In this study, phosphomolybdic acid (PMo12), as a photocatalyst, can enhance the synthesis of neutral lipids and PUFAs by influencing the expression of lipid metabolism-related genes and photosynthesis in P. tricornutum. We also observed the contents of EPA and PUFA in engineered microalgae nearly doubled compared to the wild type, while neutral lipid content showed a significant increase of 69.7% in engineered microalgae. Notably, the growth rate of engineered microalgae remained comparable to that of the wild type. This work presents an effective approach to enhance the production of microalgal bioproducts, suggesting that photocatalysts such as PMo12 could serve as viable alternatives to genetic engineering technology, facilitating the commercialization of microalgal biodiesel.